A systematic literature review on the role of Islamic monetary policy in Indonesia’s economic development - Raid Azhar Romadhan; Ely Yuliana; Elrizky Elsa Wisnuna (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
This study examines the relationship between Islamic monetary policy and Indonesia’s economic development through a systematic literature review (SLR) approach. The research aims to identify how Islamic monetary instruments contribute to achieving national economic goals of justice, equality, and sustainable growth. Data were collected from thirteen indexed journal publications in Scopus, DOAJ, and Sinta databases that discuss Islamic monetary policy and its role in Indonesia’s economy. The results show that Islamic monetary instruments such as the Wadiah Bank Indonesia Certificate (SWBI) and the Interbank Mudarabah Investment Certificate (IMA) enhance liquidity management, stabilize prices, reduce unemployment, and promote equitable wealth distribution. The findings indicate that Islamic monetary frameworks contribute significantly to financial stability, real-sector productivity, and social welfare. However, structural and institutional challenges remain, including regulatory inconsistencies and limited integration between Islamic banking and national monetary policy. The study contributes theoretically by reinforcing the role of Sharia-based instruments in achieving maqasid al-shariah and practically by offering insights for policymakers to strengthen coordination, financial literacy, and innovation in Sharia-compliant monetary mechanisms. Future research should incorporate empirical and econometric models to assess the quantitative impact of Islamic monetary policy on key macroeconomic indicators such as inflation, employment, and GDP growth.